2018
DOI: 10.3389/fpsyg.2018.02064
|View full text |Cite
|
Sign up to set email alerts
|

Measurement Invariance of the Depression Anxiety Stress Scales-21 Across Gender in a Sample of Chinese University Students

Abstract: The Depression Anxiety Stress Scales-21 (DASS-21) has three 7-item subscales (depression, anxiety, and stress). The current study aims assess the gender-based measurement invariance of the DASS-21 questionnaire in a Chinese university student sample from five different cities. The sample was composed of 13208 participants (62.3% female, mean age of 19.7 years, and SD age = 1.8). Multi-group confirmatory factor analysis supported full measurement invariance for the three subscales. The findings support the meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
61
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(76 citation statements)
references
References 36 publications
10
61
0
5
Order By: Relevance
“…Because the DASS-21 scale measures negative affective emotion similarly for both females and males, it is not necessary to use different normative scores between genders. These results are consistent with the results of Gomez et al (2014), who used an Australian sample (mean age = 47.37 years) to prove that the DASS-21 is gender-invariant, as demonstrated by Lu et al (2018), who used a sample of Chinese college students (mean age = 19.7 years) to prove that that the DASS-21 was genderinvariant. Although the factor model used are different, Gomez et al (2014) and Lu et al (2018) both used the original threefactor model, and we used a one-factor model, but our current research on a sample of Chinese hospital workers reached the same conclusion, showing that application of the DASS-21 is not influenced by gender.…”
Section: Measurement Invariance Between Genderssupporting
confidence: 89%
See 3 more Smart Citations
“…Because the DASS-21 scale measures negative affective emotion similarly for both females and males, it is not necessary to use different normative scores between genders. These results are consistent with the results of Gomez et al (2014), who used an Australian sample (mean age = 47.37 years) to prove that the DASS-21 is gender-invariant, as demonstrated by Lu et al (2018), who used a sample of Chinese college students (mean age = 19.7 years) to prove that that the DASS-21 was genderinvariant. Although the factor model used are different, Gomez et al (2014) and Lu et al (2018) both used the original threefactor model, and we used a one-factor model, but our current research on a sample of Chinese hospital workers reached the same conclusion, showing that application of the DASS-21 is not influenced by gender.…”
Section: Measurement Invariance Between Genderssupporting
confidence: 89%
“…Employing a categorical CFA (CCFA), Jafari et al (2017) found that the DASS-21 is gender-based measurement invariance among medical students, although the psychological distress of medical students is higher than the general population. In addition, using WLSMV to analyze the data of the DASS-21, Lu et al (2018) found support for gender-based measurement invariance in a Chinese sample. However, the samples of this study are students mainly from normal universities.…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations
“…Un hecho notorio es que la muestra con la que se trabajó estuvo constituida en su totalidad por estudiantes de Psicología, por lo cual los resultados no pueden ser extrapolados ni a estudiantes de otras carreras ni a la población general. Asimismo, el tamaño de la muestra no permitió realizar un análisis de invarianza entre varones y mujeres (Lu et al, 2018) ni permitió que los análisis confirmatorio y exploratorio se realizaran en submuestras distintas. Además, si bien el estimador utilizado para realizar el AFC (WLSMV) es considerado el más adecuado cuando se trabaja con indicadores de naturaleza ordinal (Brown, 2015;Byrne, 2012), existen al menos tres limitaciones analíticas asociadas a este estimador.…”
Section: Discussionunclassified